2020
DOI: 10.1016/j.ijmecsci.2020.105668
|View full text |Cite
|
Sign up to set email alerts
|

Actively controllable topological phase transition in phononic beam systems

Abstract: Topological insulators, which allow edge or interface waves but forbid bulk waves, have revolutionized our scientific cognition of acoustic/elastic systems. Due to their nontrivial topological characteristics, edge (interface) waves are topologically protected against defects and disorders. This superior and unique characteristic could lead to a wealth of new opportunities in applications of quantum and acoustic/elastic information processing. However, current acoustic/elastic topological insulators are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…For example, Sui et al [ 26 ] designed a new 2D magnetoelastic PnC plate to tune the pseudo‐spin Hall edge mode by applying an external static magnetic field and demonstrated the reconfigurable propagation path and topological robustness of the edge state through numerical simulations. Zhou et al [ 27 ] actively controlled the characteristic frequency of the resulting topologically protected edge pattern by applying an appropriate external voltage. Kurganov et al [ 28 ] proposed a topological edge state manipulation method based on temperature modulation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sui et al [ 26 ] designed a new 2D magnetoelastic PnC plate to tune the pseudo‐spin Hall edge mode by applying an external static magnetic field and demonstrated the reconfigurable propagation path and topological robustness of the edge state through numerical simulations. Zhou et al [ 27 ] actively controlled the characteristic frequency of the resulting topologically protected edge pattern by applying an appropriate external voltage. Kurganov et al [ 28 ] proposed a topological edge state manipulation method based on temperature modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, due to the main disadvantages of narrow working range with the single frequency points for the TIS in the previous 1D topological PnC systems, a theme of studying tunable TIS to realize the controllable and programmable wave manipulation has drawn increasing attention. Zhou et al [31][32][33] proposed a 1D active topological PnCs made of a homogeneous central epoxy central beam/rod sandwiched by two piezoelectric beams/rods, in which the tunable TIS could be realized by adjusting the capacitors of the periodic electric circuits. Chen et al [34] demonstrated low-frequency tunable TIS for longitudinal wave by utilizing soft topological phononic crystals, in which the tunability is achieved based on the applied axial force field.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Spadoni et al constructed the two-dimensional periodic piezoelectrical meta-plate to analyze wave propagation control of the shunted circuit 33 , which was confirmed experimentally 34 . Zhou et al proposed a periodic piezoelectric rod 35 and beam metastructure 36 to obtain tunable topological interface states for longitudinal and flexural elastic waves via employing electrical shunting circuits, respectively. The locally resonant sub-structure can be utilized to realize the lower frequency bandgap in the sub-wavelength region.…”
Section: Introductionmentioning
confidence: 99%